RGFP966 Suppresses Tumor Growth and Migration Through Inhibition of EGFR Expression in Hepatocellular Carcinoma Cells in vitro - Yu X; Yang F; Jiang H; Fan L (Dove Medical Press, 2020)
Xinying Yu, 1 Fan Yang, 2 Hong Jiang, 3 Ling Fan 1 1Second Pediatric Intensive Care Unit, Shengjing Hospital of China Medical University, Shenyang City, Liaoning Province, People’s Republic of China; 2Third Neonatal Ward, Shengjing Hospital of China Medical University, Shenyang City, Liaoning Province, People’s Republic of China; 3Second Neonatal Ward, Shengjing Hospital of China Medical University, Shenyang City, Liaoning Province, People’s Republic of ChinaCorrespondence: Xinying Yu; Ling FanShengjing Hospital of China Medical University, Shenyang City, Liaoning Province 110004, People’s Republic of ChinaTel/Fax +86 24-31939077Email fanl@sj-hospital.org; yuxinying0707@126.comPurpose: Histone deacetylase 3 (HDAC3) has been suggested to play a role in hepatocellular carcinoma (HCC). In the present report, we aimed to identify the effects of RGFP966, a specific HDAC3 inhibitor, on the cell proliferation and migration of HCC cell lines.Methods: Human HCC cell lines, which were identified using short tandem repeat (STR) DNA profiling analysis, were used in this report. Cell proliferation assay was used to identify the growth viability of cells. Wound healing and transwell assay were used to identify the migration ability of cells. Further, a human phospho-receptor tyrosine kinases array kit was used to screen out RGFP966 effects on key receptor tyrosine kinases. Then, the mRNA expression was quantified by real-time PCR, and protein expression was identified by Western blot immunoassay.Results: We found that RGFP966 inhibited both proliferation and migration of HCC cells. Further, RGFP966 represses the expression and phosphorylation levels of epidermal growth factor receptor (EGFR) in HCC cells. Moreover, HDAC3 is involved in the inhibition of EGFR by RGFP966. Overall, we elucidated an inhibitive function of RGFP966 in HCC progression.Conclusion: RGFP966 inhibits EGFR signaling pathway and suppresses proliferation and migration of HCC cells.Keywords: RGFP966, hepatocellular carcinoma, HDAC3, EGFR